2023
DOI: 10.3389/fnmol.2023.1139118
|View full text |Cite
|
Sign up to set email alerts
|

Excessive self-grooming, gene dysregulation and imbalance between the striosome and matrix compartments in the striatum of Shank3 mutant mice

Abstract: Autism is characterized by atypical social communication and stereotyped behaviors. Mutations in the gene encoding the synaptic scaffolding protein SHANK3 are detected in 1–2% of patients with autism and intellectual disability, but the mechanisms underpinning the symptoms remain largely unknown. Here, we characterized the behavior of Shank3Δ11/Δ11 mice from 3 to 12 months of age. We observed decreased locomotor activity, increased stereotyped self-grooming and modification of socio-sexual interaction compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…In contrast to acute responses, locomotor sensitization in Gad2:IFT88 KO mice was altered, though only at the lowest dose. GAD2 is expressed in both Drd1+ and Drd2+ medium spiny neurons in the rodent striatum (Ferhat et al, 2023). Activation of Drd1+ neurons is known to promote locomotion (Freeze et al, 2013;Kravitz et al, 2010), whereas Drd2+ neuron activation and DRD2 agonism can inhibit locomotion (Barrozo et al, 2015;Durieux et al, 2009;Ford, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to acute responses, locomotor sensitization in Gad2:IFT88 KO mice was altered, though only at the lowest dose. GAD2 is expressed in both Drd1+ and Drd2+ medium spiny neurons in the rodent striatum (Ferhat et al, 2023). Activation of Drd1+ neurons is known to promote locomotion (Freeze et al, 2013;Kravitz et al, 2010), whereas Drd2+ neuron activation and DRD2 agonism can inhibit locomotion (Barrozo et al, 2015;Durieux et al, 2009;Ford, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In another mouse model in which Shank3 exon 11 is deleted (Shank3 Δ11/Δ11 ), authors report striatal transcriptional alterations in both dSPNs and iSPNs with downregulated genes mainly expressed by dSPNs and upregulated genes expressed by iSPNs ( Ferhat et al, 2023 ). Running a functional analysis, among the protein functions primarily affected by transcriptional alterations there are synaptic transmission and G-protein activity.…”
Section: Cellular and Molecular Mechanisms Of Repetitive Behaviormentioning
confidence: 99%
“…Concerning ASD, reports in mouse models and human postmortem brain tissue show that striatal compartments exhibit pathological alterations ( Kuo and Liu, 2017 , 2020 ). Moreover, a recent study reported a correlation between the level of self-grooming and increased striatal expression of several genes, including glutamic acid decarboxylase 2 ( Gad2 ; Ferhat et al, 2023 ), encoding GAD65, which present preferentially in axonal terminals for synthesis of GABA for vesicle release ( Esclapez et al, 1994 ; Tian et al, 1999 ). Notably, Shank3 Δ11/Δ11 and mice with a complete lack of all SHANK3 isoforms displayed an enlargement of the compartment formed by striosomes which displayed over-expressed GAD65.…”
Section: Cellular and Molecular Mechanisms Of Repetitive Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…and in autism(Langhen et al, 2014, van Rooij et al, 2018, Mc Kinnon et al, 2019, Ferhat et al, 2023. Including the putamen, the basal ganglia play important roles in regulating repetitive behaviors (notably in autism) in association with the hippocampus, the hypothalamus, but also other neuroanatomical structures of the limbic system (including the amygdala) (Gandhi et al, 2021).…”
mentioning
confidence: 99%